Perilaku Komunikasi Aparat Pemda Kabupaten dalam Pengarusutamaan Gender di Era Otonomi Daerah (Kasus pada Kabupaten Lampung Timur) - A. Khaliq; A.V.S. Hubeis; Mintarti . (Jurnal Komunikasi Pembangunan, 2009)
Main subject of this research was behavioral of communication at gender mainstreaming study case in RegionalGovernment of East Lampung District. The objectives of the research were; (1) to studied relationship betweencharacteristics of individual with perception and participation the Government staff in gender mainstreaming atregional autonomy, (2) to studied relationship between behavioral communication with perception and participationthe government staff in gender mainstreaming at regional autonomy, (3) to studied relationship betweencharacteristic of interpersonal communication with their communication behavior in gender mainstreaming atregional autonomy era. The goals of this research are to know how important behavioral, perception andparticipation to gender mainstreaming in Regional Government of East Lampung District. Respondent in thisresearch were about 68 from 676 of the structural staff in Regional Government of East Lampung District. Themethod type in this research was descriptive co-relational survey. Result of this research is indicated that there weresignificant correlation between several indicators on independent variables and perception and also participation ingender mainstreaming.